Analysis of the Influence of Financial Literacy, Lifestyle and Financial Knowledge on Personal Financial Management Behavior of Employees of PT Matoga Cipta Indonesia - Allifah Azhara Sumantri; Aulia; Cahyo Pramono (CV. Doki Course and Training, 2026)
The development of technology and easy access to financial products require employees to have good personal financial management skills. However, in reality, there are still many employees who experience difficulties in managing finances due to low financial literacy, consumptive lifestyles, and limited financial knowledge. This study aims to analyze the influence of financial literacy, lifestyle, and financial knowledge on the personal financial management behavior of PT Matoga Cipta Indonesia employees. This study uses a quantitative approach with a survey method. Data was collected through the distribution of questionnaires to 40 employees as research respondents with saturated sampling techniques. Data analysis was carried out using multiple linear regression with the help of the SPSS program. The results of the study show that financial literacy and financial knowledge have a positive and significant effect on employees' personal financial management behavior, while lifestyle has a negative and significant effect. Simultaneously, financial literacy, lifestyle, and financial knowledge have a significant effect on the personal financial management behavior of PT Matoga Cipta Indonesia employees. This research is expected to be the basis for companies to improve the financial well-being of employees through better education and financial management programs.